Минимизация и оптимизация налогообложения как элементы налогового планирования (Путеводитель предпринимателя, 2020)
The object of an article is characterization and comparative analysis of current methods of influence on the financial-economic management of enterprise as tax minimization, tax optimization and tax planning, that, overall would determine an effective mechanism for tax risks management on the enterprise to conduct business effectively.